Revisiting the Monetary Transmission Mechanism Through an Industry-Level Differential Approach - Choi, Sangyup; Willems, Tim.; Yong Yoo, Seung (Washington, D.C. : International Monetary Fund, 2022)
By combining industry-level data on output and prices with monetary policy rates for a panel of 88 countries, this paper analyzes how the effects of monetary policy vary with certain industry characteristics. Next to being interesting in their own right, our results are informative on the importance of various transmission mechanisms (as they are expected to vary systematically with the included characteristics). Rather than relying on standard monetary policy shock identification, we overcome the endogeneity problem by taking a differential approach (interacting our monetary policy measure with industry-level characteristics). Our results suggest that monetary contractions reduce output by more in industries featuring assets that are more difficult to collateralize (as predicted by the balance sheet channel) and in industries more reliant on international trade (as predicted by the exchange rate channel). Consistent with the financial accelerator mechanism, we find that the balance sheet channel becomes stronger during bad times. At the same time, we do not find evidence supporting the traditional interest rate channel of monetary policy; the same goes for the cost channel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Cycles; Economic Growth of Open Economies; Financial Institutions and Services; Monetary Policy Transmission; Monetary Policy